Building Forecast Maps of Water Quality for Main Rivers and Canals in Tien Giang Province, Vietnam - Duc, Pham Anh (GeoScience Engineering, 2015)
This study aims to enhance the mapping of forecast for water quality assessment in Mekong Delta provinces. The data from 32 sites from main rivers and canals in an area of around 2,482 km2 in Tien Giang Province were used for calculation and mapping. The ArcGIS 9.3 software, IDW interpolation method, hydrologic data, and water quality parameters in March (2010 – 2014) were applied to build the maps of predicting on the 2020 water quality for main rivers and canals in Tien Giang Province. The estimation was based on the Water Quality Index (WQI) with 6 parameters such as pH, total suspended solid (TSS), dissolved oxygen (DO), biochemical oxygen demand (BOD), total nitrogen (T_N), and coliform. The results showed that by the year 2020 water quality at the study area in dry season will not be improved. The finding could be a scientific reference for the selection of effective approaches to improve water quality in main rivers and canals in Tien Giang Province.